Arguments for God's Existence. - Vas, Dominic (Journal of Dharma, 1998)
Possibly many of the professors of rational rheology presume they have nothing new to learn. Many years of teaching may give people the feeling that in their respective provinces they have acquired a sort of infallibility. Human psychology is such that a calculated repetition of errors gives people the impression of unshaken truth, if not of downright infallibility. Of course, many specialists may claim that their certainty is upright rather than downright.